1981
DOI: 10.1002/pol.1981.170191010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ionizing radiation on the chemical composition, crystalline content and structure, and flow properties of polytetrafluoroethylene

Abstract: This article describes a study of ionizing radiation‐induced changes in the chemical composition, crystalline content and structure, and flow properties in polytetrafluoroethylene (PTFE). Irradiatins conducted in the presence of oxygen cause acid fluoride end groups to be formed, which on exposure to water vapor hydrolyze to form carboxylic acid end groups. Analyses by infrared (IR) spectroscopy indicate that when irradiated in a vacuum PTFE exhibits defect absorption bands which have been attributed to branch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
86
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(96 citation statements)
references
References 18 publications
9
86
0
1
Order By: Relevance
“…It is postulated that biofield energy may be acted at atomic level in the treated thymol and induced perfect arrangement in the crystals that caused alteration in crystallinity. It was previously reported that high energy radiation treatment appreciably increases the crystallinity in polyethylene and polytetrafluoroethylene [37][38][39]. Similarly, in the present work biofield energy might be acted as a cross linker in thymol and led the formation of crystalline entanglements which enhanced the crystallinity.…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 53%
“…It is postulated that biofield energy may be acted at atomic level in the treated thymol and induced perfect arrangement in the crystals that caused alteration in crystallinity. It was previously reported that high energy radiation treatment appreciably increases the crystallinity in polyethylene and polytetrafluoroethylene [37][38][39]. Similarly, in the present work biofield energy might be acted as a cross linker in thymol and led the formation of crystalline entanglements which enhanced the crystallinity.…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopymentioning
confidence: 53%
“…Besides these peroxy radicals, carbonyl fluoride groups are also formed which hydrolyse in the presence of atmospheric moisture to form carboxylic acid groups (-COOH). The complete reaction mechanism can be found in [33]. Chemical changes introduced in PTFE after exposure to electron treatment were monitored by FTIR spectroscopy.…”
Section: Effect Of Modification On the Molecularmentioning
confidence: 99%
“…A search for photoproducts of perfluoro-2H-3-oxa-heptane (3) produced upon UV irradiation was made using FTIR, 1 H NMR, 19 F NMR, GC, and GC/MS techniques. Two characteristic bands were observed from FTIR analysis of the photoproducts of 3 upon irradiation at both 254 nm and 185 nm under an air-saturated condition, as shown in spectrum d of Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…F NMR measurements. CFCl 3 was employed as an internal reference and calibrated as 0 ppm for the 19 F NMR experiments. The gas chromatography (GC) analyses were performed on a Varian 3900 gas chromatograph using a Varian Facter 4 capillary column or a WCOT fused silica column coating with CP-Sil 5 CB LOW BLEED/MS (25 m x 0.25 mm).…”
Section: Spectroscopic Characterizationmentioning
confidence: 99%